Comparison of Pr-doped Ca 122 and Ca 112 Pnictides byLow-field Microwave Absorption Spectroscopy. Issue 1684 (11th September 2014) - Howard, Austin R.; Yuen, Jonathan D.; Lv, Bing; Salamon, Myron; Chu, Ching-Wu; Zakhidov, Anvar A.
ABSTRACT: Praseodymium doped CaFe2 As2 (122 structure) and CaFeAs2 (112 structure) are characterized by modulated Low Magnetic Field Microwave Absorption (LFMA) spectroscopy. In both (Pr, Ca)122 and (Pr, Ca)112 structures, a strong hysteretic LFMA is found, with a T c H of ∼30 K and ∼26 K, respectively. However, in (Pr, Ca)122, measurements also show an unusual Narrow Peak (NP) LFMA signal appearing at higher temperatures, above the lower T c H superconducting state until a T c NP of 49 K. We associate this NP LFMA with interfacial superconductivity, which has been found previously by highly anisotropic magnetization measurements. Furthermore, the absence of NP in (Pr, Ca)112 correlates with the absence of an interfacial phase. These results give useful information about the microwave signature of interfacial superconductivity present in the (Pr, Ca)122 system, and may form a roadmap towards a stabilized high temperature superconducting phase in pnictides.